Therapeutic Perspectives on the Modulation of G-Protein Coupled Estrogen Receptor, GPER, Function - Rouhimoghadam, Milad; Lu, Anh S.; Salem, Aliasger K.; Filardo, Edward J. (Frontiers in Endocrinology, 2020)
Estrogens exert their physiological and pathophysiological effects via cellular receptors, named ERα, ERβ, and G-protein coupled estrogen receptor (GPER). Estrogen-regulated physiology is tightly controlled by factors that regulate estrogen bioavailability and receptor sensitivity, while disruption of these control mechanisms can result in loss of reproductive function, cancer, cardiovascular and neurodegenerative disease, obesity, insulin resistance, endometriosis, and systemic lupus erythematosus. Restoration of estrogen physiology by modulating estrogen bioavailability or receptor activity is an effective approach for treating these pathological conditions. Therapeutic interventions that block estrogen action are employed effectively for the treatment of breast and prostate cancer as well as for precocious puberty and anovulatory infertility. Theoretically, treatments that block estrogen biosynthesis should prevent estrogen action at ERs and GPER, although drug resistance and ligand-independent receptor activation may still occur. In addition, blockade of estrogen biosynthesis does not prevent activation of estrogen receptors by naturally occurring or man-made exogenous estrogens. A more complicated scenario is provided by anti-estrogen drugs that antagonize ERs since these drugs function as GPER agonists. Based upon its association with metabolic dysregulation and advanced cancer, GPER represents a therapeutic target with promise for the treatment of several critical health concerns facing Western society. Selective ligands that specifically target GPER have been developed and may soon serve as pharmacological agents for treating human disease. Here, we review current forms of estrogen therapy and the implications that GPER holds for these therapies. We also discuss existing GPER targeted drugs, additional approaches towards developing GPER-targeted therapies and how these therapies may complement existing modalities of estrogen-targeted therapy.